2017
DOI: 10.18203/2394-6040.ijcmph20172093
|View full text |Cite
|
Sign up to set email alerts
|

A study on the morbidity pattern in adolescent school girls

Abstract: Background: The World Health Organization (WHO) has defined adolescence as the age group of 10-19 years. According to World Health Organisation, adolescents constitute about one fifth of the world population, and in India they constitute about 21% of the total population. Adolescent girls are the worst sufferers of various forms of malnutrition because of their increased nutritional needs and low social power. If their nutritional needs are not met, they are likely to give birth to undernourished children, thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
1
4
1
Order By: Relevance
“…6 Sinha et al in Lucknow, found vaginal discharge in 8.1%, which is higher than in present study. 13 Nirmala et al in Kerala found endocrinal problems including thyroid enlargement in 7.5% among unmarried girls between 16-18 years of age from urban area, this is much higher than 0.91% in present study, which may be due to majority of girls during their early adolescence in our study. 20 Sachan et al in Lucknow found religion and type of family were insignificantly related to total morbidity among girls, however in present study general morbidity was significantly more among girls belonging to nuclear families and Muslim/others group when respectively compared with girls from joint families and Hindu girls.…”
Section: Meancontrasting
confidence: 63%
See 1 more Smart Citation
“…6 Sinha et al in Lucknow, found vaginal discharge in 8.1%, which is higher than in present study. 13 Nirmala et al in Kerala found endocrinal problems including thyroid enlargement in 7.5% among unmarried girls between 16-18 years of age from urban area, this is much higher than 0.91% in present study, which may be due to majority of girls during their early adolescence in our study. 20 Sachan et al in Lucknow found religion and type of family were insignificantly related to total morbidity among girls, however in present study general morbidity was significantly more among girls belonging to nuclear families and Muslim/others group when respectively compared with girls from joint families and Hindu girls.…”
Section: Meancontrasting
confidence: 63%
“…5 However, skin diseases in study by Yerpude et al in Guntur, Andhra Pradesh was 22.2% among urban school adolescent girls, 10.5% in Hari Krishna et al's study, and 3.1% in Sinha et al's study. [11][12][13] Refractive errors in present study were present in 31.17% girls with significantly more of rural girls affected as compared to urban, with the visual acuity varying from 6/9 to 6/36 in better eye. Inadequate correction was detected in 26 girls of which 17 were rural and 9 urban.…”
Section: Meanmentioning
confidence: 77%
“…9 Sinha et al in a study conducted on Adolescent girls in Lucknow district found that eye problem was seen in 31% of adolescent girls. 10 In the present study more of urban school going adolescent girls (3.2%) had Hypertension as compared to (2.5%) of rural area and 12.5% adolescent girls were found to be prehypertensive. Similar findings were seen by Mohan et al in school going children of Ludhiana, Punjab found that prevalence of sustained hypertension was 6.69% in urban and in rural area it was 2.56%.…”
Section: Discussionsupporting
confidence: 39%
“…The major health problems in adolescent age group in India are cited to be nutrient deficiency, macro-nutrient deficiency resulting in underweight (51%) and stunting (34%), micro-nutrient deficiencies especially iron deficiency resulting in anaemia, more common in girls (38.45%). 6 Important health issues which are more common in school going adolescents are malnutrition (31%), psychological problems (34%) including stress (27.3%), anxiety (38.7%), depression (31.9%), social phobia (27%), eye problem (31%), dental problem (35.34%) and in female menstrual problem accounting for 79.5%. Other health issue are skin diseases, tonsillitis, respiratory diseases and ear diseases.…”
mentioning
confidence: 99%
See 1 more Smart Citation